Addition of soybean meal extract with Lactobacillus plantarum in rations on protein digestibility and performance of broiler chickens - R. Afro'; V. D. Y. B. Ismadi; L. Krismiyanto; M. Mulyono (Journal of the Indonesian Tropical Animal Agriculture, 2023)
This study examined the effect of adding soybean meal extract (SME) and Lactobacillus plantarum (LP) on protein digestibility and performance of broiler chickens. The material used was 8-day-old Cobb CP 707 strain broilers with a body weight of 137.89 ± 3.7 g. This study used a completely randomized design with 6 treatments and 4 replicates, with each replicate of 8 birds. The treatments were T0: basal diet (control), T1: basal diet + LP 1.2%, T2: basal diet + SME 0.15%, T3: basal diet + SME 0.30%, T4: basal diet + SME 0.15% + LP 1.2%, T5: basal ration + SME 0.30% + LP 1.2%. Parameters measured were the performance of broiler chickens, lactic acid bacteria population, Escherichia coli population, intestinal pH, protein consumption, protein digestibility, and antioxidant activity. The results showed that the addition of SME and Lactobacillus plantarum in the ration had a significant effect (P <0.05) on total daily weight gain, total daily feed intake, total feed conversion, lactic acid bacteria population, Escherichia coli population, intestinal pH, protein consumption, protein digestibility, and antioxidant activity. Significantly higher total daily weight gains were observed in T5 (54.09 g) compared to T3 (51.27 g), T2 (46.98 g), T1 (46.64 g), and T0 (45.56 g). Total daily feed intake of T5 (79.94 g) was significantly higher those of T2 (74.52 g), T1 (74.17 g), and T0 (74.89 g). Feed conversion ratio was significantly lower in T5 (1.48) compared to the others, but not different from T4 (1.54). The LAB population of T5 (10.26 log cfu/g) was significantly higher than those of T2 (8.98 log cfu/g), T1 (8.99 log cfu/g), and T0 (6.99 log cfu/g). The Escherichia coli population of T5 (1.50 log cfu/g) was significantly lower than T1 (2.40 log cfu/g) and T0 (4.54 log cfu/g). Intestinal pH of T5 (5.90) was significantly lower than the others, but not different from T4 (5.91). Protein consumption of T5 (17.14 g) was significantly higher than T2 (15.98 g), T1 (15.90 g), and T0 (16.00 g), and protein digestibility of T5 (88.53%) was significantly higher than T2 (85.42%), T1 (82.92%), and T0 (80.37%). Malondialdehyde of T5 (0.80 nmol/ml) was significantly lower than T2 (1.01 nmol/ml), T1 (1.03 nmol/ml), and T0 (1.27 nmol/ml). Superoxide dismutase of T5 (21.43 U/ml) was significantly higher than all treatments. The study concludes that adding soybean meal extract with 0.30% and Lactobacillus plantarum 1,2% (T5) was effective in increasing protein digestibility and optimizing performance in broiler chickens.